2018
DOI: 10.1111/jerd.12363
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength of universal adhesives to flat versus Class I cavity dentin with pulpal pressure simulation

Abstract: Microtensile bond strength to dentin of universal adhesives appears more stable following the "self-etch" than "total-etch" protocol after long-term degradation. More clinically relevant data may be obtained using simulated pulpal pressure and cavity-type sample preparation in the study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For ABU, however, the ER strategy resulted in higher bond strengths although considerable heterogeneity was noted among the included studies . Contrastingly, studies utilizing artificial‐aging for testing dentin bond durability of UAs concluded that the SE strategy resulted in more stable long‐term bond characteristics . Studies have attributed this to the stable chemical bonding produced by 10‐MDP .…”
Section: Resultsmentioning
confidence: 99%
“…For ABU, however, the ER strategy resulted in higher bond strengths although considerable heterogeneity was noted among the included studies . Contrastingly, studies utilizing artificial‐aging for testing dentin bond durability of UAs concluded that the SE strategy resulted in more stable long‐term bond characteristics . Studies have attributed this to the stable chemical bonding produced by 10‐MDP .…”
Section: Resultsmentioning
confidence: 99%
“…Simulated pulpal pressure and Class 1 preparation may be recommended for adhesive strength tests. The values obtained were in the range of 19-42 MPa initially and 16-36 MPa after 6 months storage 28 .…”
Section: Discussionmentioning
confidence: 86%
“…4,23 Nevertheless, when adhesive interfaces were subjected to aging processes, several studies concluded that the self-etch approach resulted in more stable long-term bond characteristics. 6,9,24 One meta-analysis of in vitro studies that evaluated nanoleakage related to universal adhesives reported divergent results and highlighted that etching modes influenced significantly and dissimilarly the nanoleakage of universal adhesives. Namely, the etch-and-rinse technique significantly reduced the nanoleakage of the Peak Universal and G-Bond Plus adhesives, whereas the self-etch mode reduced the nanoleakage of All-Bond Universal.…”
Section: Discussionmentioning
confidence: 99%